2021
DOI: 10.1108/jiabr-10-2020-0328
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers and bivariate portfolios of gold-backed cryptocurrencies and gold during the COVID-19 outbreak

Abstract: Purpose This paper aims to analyze the time-varying connectedness of gold-backed cryptocurrencies and gold. This study determines the volatility spillovers in these two asset classes and the performance of bivariate portfolios based on net pairwise spillovers. Design/methodology/approach This research uses two Islamic and four conventional gold-backed cryptocurrencies and gold as variables. GJR-GARCH method under corrected DCC (cDCC) of Aielli (2013) evaluates the dynamic connectedness. Additionally, the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Likewise, Lahmiri & Bekiros (2019) reported that green and Islamic cryptocurrencies showed anti-persistence in their returns while the volume, prices, and volatility exhibit a higher pertinence dynamic than its counterpart. During economic meltdown due to COVID-19 (Nugroho, 2021), Islamic gold-backed cryptocurrency (GC-gold) has shown better performance than conventional GC-gold, which is indicated by the resistance of Islamic GC-gold to COVID-19's impact. Moreover, Chkili et al (2021) found that bitcoin provides a safer asset for investors during economic downturns than Islamic stock.…”
Section: Gjr-garch Methods Under Corrected DCC (Cdcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Lahmiri & Bekiros (2019) reported that green and Islamic cryptocurrencies showed anti-persistence in their returns while the volume, prices, and volatility exhibit a higher pertinence dynamic than its counterpart. During economic meltdown due to COVID-19 (Nugroho, 2021), Islamic gold-backed cryptocurrency (GC-gold) has shown better performance than conventional GC-gold, which is indicated by the resistance of Islamic GC-gold to COVID-19's impact. Moreover, Chkili et al (2021) found that bitcoin provides a safer asset for investors during economic downturns than Islamic stock.…”
Section: Gjr-garch Methods Under Corrected DCC (Cdcc)mentioning
confidence: 99%
“…Hence, the result might not be robust. (Nugroho, 2021) This study examines volatility spillover between gold-backed cryptocurrencies and gold, particularly during COVID-19.…”
Section: Empirical Mode Decompositionmentioning
confidence: 99%
“…Finally, the analysis of hedging effectiveness suggests that investors can reduce the risk of Islamic sectorial equity portfolios by adding the Islamic Sharia-based cryptocurrencies. Nugroho (2021) reports that the dynamic spillover between gold and gold-backed cryptocurrencies has been increased during COVID-19 pandemic. Moreover, the gold is the net volatility receiver during the same period.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, several works have studied the phenomenon of volatility transmission between commodities, Islamic and conventional stocks and cryptocurrencies markets (Abbes and Trichilli, 2015; Yi et al , 2018; Trichilli et al , 2018; Trichilli et al , 2020; Catania and Sandholdt, 2019; Mensi et al , 2020; Trichilli and Boujelbène Abbes, 2022). There are also several studies that examine the contagion risks and spillover effects in conventional and Islamic gold-backed cryptocurrencies markets as the studies of Yousaf and Yarovaya (2021) and Nugroho (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Green bonds could act as a safe haven during the outbreak (Hacı€ omero glu et al, 2021). Similarly, the green bond market was also more efficient during the epidemic, demonstrating that green bonds can act as a good diversifier for stock investors during market turmoil (Arif Model Functional forms Abbreviation DCC-t-Copula (Antonakakis et al, 2020;Nugroho, 2021b;Patton, 2006) x…”
Section: Functional Forms Of Covariance Matricesmentioning
confidence: 99%